Mechanisms and new advances in the efficacy of plant active ingredients in tendon-bone healing - Yuan Li; Wei Wang; Wensheng Xu (Journal of Orthopaedic Surgery and Research)
Abstract The tendon-bone interface, known as the tenosynovial union or attachment, can be easily damaged by excessive exercise or trauma. Tendon-bone healing is a significant research topic in orthopedics, encompassing various aspects of sports injuries and postoperative recovery. Surgery is the most common treatment; however, it has limited efficacy in promoting tendon-bone healing and carries a risk of postoperative recurrence, necessitating the search for more effective treatments. Recently, plant-active ingredients such as tanshinone IIA, astragaloside, ginsenoside Rb1, and resveratrol have garnered significant attention due to their unique advantages in promoting tendon-bone healing. This review outlines the various mechanisms and research progress of these four plant-active ingredients, as well as compound ingredients, in promoting tendon-bone healing. For instance, tanshinone IIA significantly accelerates the healing rate and improves healing quality through anti-inflammatory, antioxidant, and cell proliferation-promoting mechanisms. Astragaloside expedites tendon-bone healing and enhances the mechanical strength of healing tissues primarily through anti-inflammatory, antioxidant, and immunoregulatory effects. Ginsenoside Rb1 enhances local blood supply and facilitates tendon-bone tissue repair through angiogenesis, anti-inflammatory, and antioxidant pathways. Resveratrol protects cellular function and accelerates tissue healing due to its potent antioxidant and anti-inflammatory effects. Additionally, the mechanisms and progress of certain Chinese herbal compound components in tendon-bone healing are outlined. This review concludes that these four plant-active ingredients and herbal compound components promote tendon-bone healing through various mechanisms. The efficacy mechanisms and research progress of these plant-active ingredients are summarized to provide references for clinical treatment and related research.